gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Effects of intramammary infusion of Minthostachys verticillata essential oil in cows at drying-off on microbiological and immunological parameters, and milk quality during the subsequent lactation - Sofía Arsaute; Elina B. Reinoso; María E. Cecchini; Ivana D. Montironi; Dardo A. Roma; Fabiana D Éramo; Marcela Moressi; Lorena Decara; Javier Macchiavelli; Andrea Ariño; Laura Noelia Cariddi (Veterinary Research Communications, 2025)

Evaluation of oral supplementation of free and nanoencapsulated Minthostachys verticillata essential oil on immunological, biochemical and antioxidants parameters and gut microbiota in weaned piglets - Ivana D. Montironi; Sofía Arsaute; Dardo A. Roma; María E. Cecchini; Agustina Pinotti; Fernando Mañas; Fernando A. Bessone; Alejandra de Moreno de LeBlanc; Fabrisio E. Alustiza; Romina V. Bellingeri; Laura Noelia Cariddi (Veterinary Research Communications, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Active microbial ecosystem in Iron‐Age tombs of the Etruscan civilization - Angela Cirigliano; Francesco Mura; Adele Cecchini; Maria Cristina Tomassetti; Daniele Federico Maras; Monica Di Paola; Niccolò Meriggi; Duccio Cavalieri; Rodolfo Negri; Andrea Quagliariello; John E. Hallsworth; Teresa Rinaldi (Environmental Microbiology, 2021)
Summary Earth's microbial biosphere extends down through the crust and much of the subsurface, including those microbial ecosystems located within cave systems. Here, we elucidate the microbial ecosystems within anthropogenic 'caves'; the Iron‐Age, subterranean tombs of central Italy. The interior walls of the rock (calcium‐rich macco ) were painted ~2500 years ago and are covered with CaCO 3 needles (known as moonmilk). The aims of the current study were to: identify biological/geochemical/biophysical determinants of and characterize bacterial communities involved in CaCO 3 precipitation; challenge the maxim that biogenic activity necessarily degrades surfaces; locate the bacterial cells that are the source of the CaCO 3 precipitate; and gain insight into the kinetics of moonmilk formation. We reveal that this environment hosts communities that consist primarily of bacteria that are mesophilic for temperature and xerotolerance (including Actinobacteria, Bacteroidetes and Proteobacteria); is populated by photosynthetic Cyanobacteria exhibiting heterotrophic nutrition ( Calothrix and Chroococcidiopsis ); and has CaCO 3 precipitating on the rock surfaces (confirmation that this process is biogenic) that acts to preserve rather than damage the painted surface. We also identified that some community members are psychrotolerant ( Polaromonas ), acidotolerant or acidophilic (members of the Acidobacteria ), or resistant to ionizing radiation ( Brevundimonas and Truepera ); elucidate the ways in which microbiology impacts mineralogy and vice versa ; and reveal that biogenic formation of moonmilk can occur rapidly, that is, over a period of 10 to 56 years. We discuss the paradox that these ecosystems, that are for the most part in the dark and lack primary production, are apparently highly active, biodiverse and biomass‐rich.

Variation in fructooligosaccharide contents during plant development and in different cultivars of durum wheat - A. Paradiso; C. Cecchini; E. Greco; M. G. D'Egidio; L. De Gara (Plant Biosystems, 2008)

Force responses to fast ramp stretches in stimulated frog skeletal muscle fibres - M. A. Bagni; G. Cecchi; E. Cecchini; B. Colombini; F. Colomo (Journal of Muscle Research and Cell Motility, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)